Gender, ICTs and health in the Caribbean - Muturi, Nancy W. (KIT (Royal Tropical Institute); Oxfam GB, 2011)
This chapter explores access and use of ICTs in the Caribbean, paying special attention to their role in the promotion of gender and health issues in the region, and specifically in Jamaica. In Jamaica progress in the use of ICTs is visibly more advanced than in the other countries. The Jamaican government has fully supported this progress financially and technically, implementing policies to support the application and use of ICTs in national development. Jamaica has set the tone for the other Caribbean countries, particularly Trinidad and Tobago, Barbados and Guyana where ICT policies and IT strategic plans are currently in place. The chapter largely focuses on the internet because of its widespread influence.
Keywords: Information technology; Gender; ICT; Caribbean